2017
DOI: 10.1111/fwb.12947
|View full text |Cite
|
Sign up to set email alerts
|

Atlantic salmon (Salmo salar) and brown trout (Salmo trutta) differ in their suitability as hosts for the endangered freshwater pearl mussel (Margaritifera margaritifera) in northern Fennoscandian rivers

Abstract: European populations of the freshwater pearl mussel (FPM, Margaritifera margaritifera) have collapsed across much of the species’ geographic range and, despite many types of conservation intervention, the number of successful restoration efforts has been low. The goal of this study was to determine whether there were population‐specific differences in the suitability of Atlantic salmon (Salmo salar) and brown trout (S. trutta) as hosts for the parasitic glochidium larvae of FPM. We predicted that such differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 58 publications
(118 reference statements)
4
35
2
Order By: Relevance
“…Thus, one conclusion of this study is that there appears to be one dominant host species for the parasitic phase of the M. margaritifera life cycle, but that the primary host varies among rivers. Similar findings have been reported from Scandinavia (Karlsson, Larsen, & Hindar, ; Larsen, Hårsaker, Bakken, & Barstad, ; Salonen et al, ). Although efforts were made to ensure that selected sites on each river had habitat for both salmon and trout juveniles, it is acknowledged that the relative abundance of each species at each site is likely to reflect local habitat type; however, for five rivers sufficient numbers of both species were collected to make meaningful comparisons between the species.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, one conclusion of this study is that there appears to be one dominant host species for the parasitic phase of the M. margaritifera life cycle, but that the primary host varies among rivers. Similar findings have been reported from Scandinavia (Karlsson, Larsen, & Hindar, ; Larsen, Hårsaker, Bakken, & Barstad, ; Salonen et al, ). Although efforts were made to ensure that selected sites on each river had habitat for both salmon and trout juveniles, it is acknowledged that the relative abundance of each species at each site is likely to reflect local habitat type; however, for five rivers sufficient numbers of both species were collected to make meaningful comparisons between the species.…”
Section: Discussionsupporting
confidence: 88%
“…Other studies have explored population‐specific differences of Margaritifera margaritifera and found differences in host species suitability in Fennoscandian rivers between populations in large main channels and small tributaries (Salonen et al, ). They have suggested that populations in north‐west Scotland may differ in their cues for attachment to a host (Clements, Thomas, & Adams, ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an enhanced ventilation rate in fish infected with glochidia is likely to be a plausible mechanism explaining their higher vulnerability to the D. pseudospathaceum infection. In addition, June–July, when subsequent infections with D. pseudospathaceum cercariae were performed, is the period when freshwater pearl mussel glochidia detach from fish (Salonen et al., )—an event that typically damages gills as glochidial cysts rupture. This should further increase the vulnerability of fish to D. pseudospathaceum cercariae.…”
Section: Discussionmentioning
confidence: 99%
“…The freshwater pearl mussel, Margaritifera margaritifera is a freshwater bivalve critically endangered through its native range (Geist, ; Lopes‐Lima et al., ). This bivalve has an obligate parasitic larval stage, the glochidium, which attaches to gills of salmonid fishes, such as Atlantic salmon ( Salmo salar ) and brown trout ( Salmo trutta ) (Salonen, Marjomäki, & Taskinen, ; Salonen et al., ; Taeubert & Geist, ). The latter fish is the exclusive host for freshwater pearl mussel glochidia in many Central European populations (Geist, Porkka, & Kuehn, ; Taeubert & Geist, ).…”
Section: Introductionmentioning
confidence: 99%